2021
DOI: 10.1111/ijfs.15166
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of novel small molecule umami peptide from ovotransferrin

Abstract: Summary Umami ingredients are the important components of seasoning in food and widely used in food production. However, few novel umami peptides were isolated and identified. Here, the purpose of this research is to identify small molecule umami peptides derived from ovotransferrin by molecular docking. Based on the virtual enzymatic hydrolysis and molecular docking analysis, the tripeptide DEK with the lowest CDOCKER‐ENERGY (−99.50 kcal mol−1) was identified, which could occupy the extracellular venus flytra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…28,29 The signals of these umami receptors appeared in different positions of the tongue, which indicated that their functions are different. 30,31 Umami is a chemical process induced when an umami-producing substance activates the T1R1/T1R3 umami receptor. This activation alters the membrane potential and causes the transmission of the umami signal to the brain's taste region through the umami nerve.…”
Section: Modular Docking Of Peptides With T1r1/t1r3mentioning
confidence: 99%
“…28,29 The signals of these umami receptors appeared in different positions of the tongue, which indicated that their functions are different. 30,31 Umami is a chemical process induced when an umami-producing substance activates the T1R1/T1R3 umami receptor. This activation alters the membrane potential and causes the transmission of the umami signal to the brain's taste region through the umami nerve.…”
Section: Modular Docking Of Peptides With T1r1/t1r3mentioning
confidence: 99%
“…Subsequently, T1R1/T1R3 (Li et al., 2002; Nelson et al., 2002) and taste‐mGluR1 (San Gabriel et al., 2005) were also confirmed to be umami taste receptors. Studies have shown that the mGluRs signal primarily appears at the posterior part of tongue, which helps distinguish umami from other taste substances, whereas the T1R1/T1R3 signal mainly appears at the front part of the tongue, which plays significant role in preference behavior (Kalyanasundar et al., 2020; Yasumatsu et al., 2012; Zhao et al., 2021). It was reported that the umami receptors from different tongue regions exhibited the difference in sensing ability to MSG and IMP (Fan et al., 2022).…”
Section: Umami Receptormentioning
confidence: 99%
“…On the basis of virtual enzymatic hydrolysis and molecular docking analysis, Zhao et al. (2021) identified the umami‐flavored tripeptide DEK from ovotransferrin, which could occupy the VFTD of T1R1, and found that the amino acids Asp147 and Arg151 of T1R1 may play a crucial part in the reaction of T1R1/T1R3 with DEK. In a study by Dang, Hao, Cao, et al.…”
Section: Screening Of Umami Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry‐cured products usually contain umami substances, including free amino acids, umami peptides, organic acids and nucleotides (Zhang et al ., 2021a; Wang et al ., 2022). Among those umami molecules, umami peptides generally exist in the product with the processing of dry curing (Fan et al ., 2021; Zhao et al ., 2021; Zhu et al ., 2021). In literature, CCNKSV and AHSVRFY were isolated from dry‐cured ham and they exhibited a good umami taste by the evaluation of electronic tongue (Dang et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%